EMPOWERMENT OF FINANCIAL MANAGEMENT AND UTILIZATION OF ARTIFICIAL INTELLIGENCE TO SUPPORT GLOBAL MARKET PENETRATION AT BIG BEE FARM AGRITOURISM, THAILAND - Gema Ika Sari; Bambang Dwi Suseno; Sasithorn Suwandee; Hidayatullah Hidayatullah; Nining Sulastri Kurnia; Riani Puasarin; Fitriyansyah Fitriyansyah; Nani Rohaeni (International Journal of Engagement and Empowerment (IJE2), 2026)
This Community Service Program (PkM) aims to empower financial management practices and optimize the utilization of Artificial Intelligence (AI) to support global market penetration at Big Bee Farm Agritourism, Thailand. The program addresses key challenges such as weak financial governance, limited digital literacy, and low adoption of advanced technologies that hinder the competitiveness of agritourism enterprises in the global market. A participatory approach was applied through field observation, training, mentoring, and evaluation involving management and staff of the agritourism  business. The implementation of the program focused on strengthening financial management capacity, enhancing digital literacy, and introducing AI-based tools for business operations, marketing, and customer engagement. The results indicate significant improvements in financial recording systems, budgeting awareness, and financial transparency. In addition, participants demonstrated increased understanding and initial application of digital technologies and AI in supporting business activities, particularly in marketing and data utilization. Furthermore, the program contributed to expanding the business’s global market orientation through improved digital promotion strategies and enhanced readiness for international competitiveness. Although AI integration is still in the early stage, the initiative successfully initiated a transformative shift toward technology-driven agritourism management. Overall, the program demonstrates that the integration of financial empowerment and digital innovation plays a crucial role in strengthening the sustainability and global competitiveness of agritourism enterprises.